STRATEGI KOMUNIKASI PERSUASIF ADMIN FACEBOOK PJBO (PEKANBARU JUAL BELI ONLINE) DALAM MENARIK MINAT MEMBER TERSURVEY DI PEKANBARU - Rendy Setiawan; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Pekanbaru Jual Beli Online or PJBO is an online group that used grou feature in social media Facebook. PJBO group page used as a place where Pekanbaru people commit online transaction in selling or buying various things and services. And over timethis group start to applying commercial function in a program named ‘member tersurvey’. ‘Member tersurvey’ program is a transaction securities guarantee from admin for the members if they pay administration cost as much as Rp 10.000,00 (ten thousand rupias) per-month. For appealing member to join this program, PJBO admin used persuasive communication strategy . This study aim to know the persuasive communication strategy that used by PJBO admin to appeal member tersurvey in Pekanbaru.The methods in this studi is descriptive qualitative. Collecting data technique with using interview, observation and documentation. This study subjects are the PJBO admins and tersurvey members. This study objects is PJBO facebook group, and documentation usede archieves and literatures that relate to this study. The results of this study indicate that the psychodynamic persuasive communication strategy used by the admin utilizes post columns in PJBO group, sociocultural strategy by utilizing the encouragement of the large number of registered traders in the survey program, and the meaning construction strategy is done by using testimony from registered traders.. Principes that used is selective exposure, and inoculation princip. Techniques that used is putting it ‘up to you’ technique, simulated disinterest technique, bandwagon technique and reassurance technique.Keywords: Strategy, Persuasive Communication, PJBO